REKONFIGURASI PENYULANG KINTAMANI UNTUK MENURUNKAN.RUGI-RUGI.DAYA.DAN JATUH TEGANGAN PADA WILAYAH KERJA ULP BANGLI - Putu Juliartawan; I Nyoman Setiawan; I Wayan Arta Wijaya (Program Studi Teknik Elektro UNUD, 2022)
The Kintamani supplay is uone of the feedersl in the PT PLN (Persero) UP3 East Bali Work Areawhich is the responsibility of ULP Bangli. This feeder uses a loop type configuration that servesconsumers in the Penelokan, Songan, Kintamani, Writing, Catur and Sukawana areas. This feederhas a channel length of 237,886 kms with a total distribution substation of 183 transformer units andthe peak load of this feeder reaches 3,160 kW. This condition causes a voltage drop of 7.68% andpower losses of 7.5%. The reconfiguration of this feeder is done by cutting the network which istransferred to Nandini's feeder. Reconfiguration by cutting the network shows an improvement in thevoltage of the Kintamani feeder which initially dropped from 7.68% to 3.27% and decreased powerlosses from 7.5% to 4.81%. Improvements in voltage and power losses that occur in this feederchange the value of the voltage drop and power losses on the Nandini feeder, which has an increasein the percentage of voltage drop from (-)1.44% to 1.27% and losses the initial power of 0.5% to2.10%. With this the Kintamani feeder is right for reconfiguration with the Nandini feeder. Thus, for theKintamani feeder and the Nandini feeder, it is in accordance with the 2017-2022 Distribution SystemMaster Plan Manual, where the maximum allowable voltage drop is a maximum of 19kV and amaximum power loss of 5%.